Keratinocyte progenitor cells reside in human subcutaneous adipose tissue. - Toshio Hasegawa; Atsushi Sakamoto; Akino Wada; Tatsuo Fukai; Hideo Iida; Shigaku Ikeda (PLoS ONE, 2015)
The differentiation of adipose-derived stem cells (ASCs) towards epithelial lineages has yet to be demonstrated using a standardized method. This study investigated whether keratinocyte progenitor cells are present in the ASC population. ASCs isolated from subcutaneous adipose tissue were cultured and examined for the expression of the keratinocyte progenitor markers p63 and desmoglein 3 (DSG3) by immunofluorescence microscopy and flow cytometry. In addition, p63 and DSG3 expression levels were assessed before and after differentiation of ASCs into adipocytes by real-time PCR and western blot analysis, as well as in subcutaneous adipose tissue by real-time reverse transcriptase polymerase chain reaction. Both markers were expressed in ASCs, but were downregulated after the differentiation of ASCs into adipocytes; p63-positive cells were also detected in subcutaneous adipose tissue. ASCs co-cultured with human fibroblasts and incubated with all-trans retinoic acid and bone morphologic protein 4 showed an upregulation in DSG3 level, which was also increased in the presence of type IV collagen. They also showed an upregulation in cytokeratin-5 level only in the presence of type IV collagen. These results provide the demonstration that keratinocyte progenitor cells reside in subcutaneous adipose tissue.